Behavior of blends of CSA and Portland cements in high chloride environment. (30th November 2020) - Bertola, Federica; Gastaldi, Daniela; Irico, Sara; Paul, Geo; Canonico, Fulvio
Highlights: The anhydrite/CSA clinker ratio is an important parameter in CSA-OPC blends. The use of seawater causes changes in the hydrated phase assemblage. AFm phases play a key role in CSA-OPC blends. Seawater can be used if the blends are formulated with a deficiency of sulfates. Abstract: Calcium SulfoAluminate (CSA) cement has received increasing interest in recent years, mainly for its environmental aspects. However, few drawbacks such as its higher cost, compared to Ordinary Portland Cement (OPC), or the high carbonation rate, limits its application in reinforced concrete even when high early strengths are required. A technological solution could be combining CSA cement with non-corrosive reinforcements, widely used for structure exposed to marine environments. In order to evaluate the feasibility of this innovative solution even in high chlorides environments, blends of CSA clinker and limestone Portland cement were investigated in combination with seawater and varying the constituent proportions. The results show that sulfates play a key role in the equilibria between AFt/AFm influencing the Friedel's salt formation, thus the ability to bind chlorides. An optimal blend composition, able to improve the durability of concrete in marine environment, is suggested.